(untitled) (Argos, 2025)
This paper discusses a fragment of Lucian’s Dialogues of the Dead 6, in which Socrates after a brief conversation with Menippus of Gadara invites the latter to lie down with himself and his beautiful dead comrades, Charmides, Phaedrus and Alcibiades. A lexical and contextual analyzes of the fragment proves that Socrates’ invitation conceals a pederastic intention. A global vision of Dialogues of the Dead and a consideration of Lucian’s poetics explain why Socrates, who loves young boys, is interested in the old and ugly Menippus of Gadara.